The Empowering the Gintangan Village Community in Realizing a Circular Economy Through the Production of Eco Enzymes (EE) and Liquid Organic Fertilizer (POC): Pemberdayaan Masyarakat Desa Gintangan dalam Mewujudkan Ekonomi Sirkular Melalui Produksi Eco Enzyme (EE) dan Pupuk Organik Cair (POC) - Asmaul Khusna; Jamilah; Nugroho Dwi Prasojo; Nurul Alfiyah; Riza Rahimi Bachtiar (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Organic waste management in Gintangan Village, Blimbingsari District, Banyuwangi, has not been fully optimized, as some household organic waste is still disposed of without prior sorting, while dry yard waste is often burned in open spaces. These practices reduce the opportunity to reuse organic materials and may contribute to local environmental problems. This community service program aimed to improve residents’ basic knowledge and practical skills, particularly among housewives, in processing household organic waste into eco enzyme and liquid organic fertilizer (POC) using a simple circular economy approach. The program was conducted through socialization, hands-on training, and direct assistance. Evaluation was carried out through observation, pre-test and post-test instruments, and organoleptic assessment of the fermented products. A total of 20 participants were involved in the activity. The initial assessment indicated that 90% of participants had limited understanding of how kitchen waste could be processed into fermentation-based products. After the training, 90% of participants were able to correctly explain and apply the 1:3:10 ratio commonly used in eco enzyme production. Participants also produced eco enzyme and POC and were able to identify basic indicators of successful fermentation, such as aroma, color, and absence of mold contamination. The results suggest that household organic waste has the potential to be processed into useful products at the household scale. This program also introduced an integrated use of green and brown organic waste as a practical effort to reduce yard waste burning and promote the reuse of locally available organic resources.